Costs and effectiveness of a culturally tailored communication training program to increase cultural competence among multi-disciplinary care management teams - Marie Parker; Xiangming Fang; Andrew Bradlyn (BMC, 2020)
Abstract Background Several studies have demonstrated that cultural competence improves patient-provider communication, which promotes adherence to established care plans and improves patient satisfaction and health outcomes. However, there is very little data available regarding the costs associated with the development and implementation of cultural competence training, or the cost-effectiveness of these programs. To that end, this evaluation aims to describe costs, program effectiveness, and cost-effectiveness of a culturally tailored communication training program to improve cultural competence among multi-disciplinary care management teams. Methods As part of a region-wide quality improvement initiative to reduce healthcare disparities among African American patients with uncontrolled hypertension, three multi-disciplinary care management teams were invited to participate in a two-part communication training program. A paired samples t-test was used to assess program effectiveness based on participant responses to a validated cultural competence self-assessment survey 2 weeks before and after the training program. A micro-costing approach was used to estimate programmatic costs for content development and delivery. Cost-effectiveness was then determined using the average cost-effectiveness ratio, and sensitivity analyses were conducted to assess the impact of participant mix on this result. Results All scores (n = 17) improved after training; however, only the culturally competent behaviors (CCB) subscale change was statistically significant (p = 0.02). Overall program costs were $5754.19. The average program cost per participant was $138.51, with an ACER of $337.83 per 1-unit increase in CCB score. Sensitivity analyses yielded a range of ACERs between $122.59 and $457.07, where all participants are support staff or nurses, respectively. Conclusions Culturally tailored communication training increases how frequently participants demonstrate culturally competent behaviors and may be a cost-effective intervention for care management teams to address individual cultural competence. Detailed costs associated with cultural competence training are largely unavailable in the literature; as such, these data may serve as a financial framework for organizations considering the implementation of similar programs.